Climate projections of precipitation and temperature in cities from ABC Paulista, in the Metropolitan Region of São Paulo—Brazil - Valverde, María Cleofé; Calado, Bianca Nunes; Calado, Gabrielle Gomes; Kuroki, Larissa Yumi; Brambila, Ricardo [UNESP]; Sousa, Aline Ramos de (Frontiers, 2023)
Cities are increasingly vulnerable to climate change's impacts and poorly adapted to extreme variability. This study aimed to evaluate climate projections of air temperature and precipitation in seven cities in the Metropolitan Region of São Paulo that correspond to the Greater ABC Paulista. We used high-resolution models Eta-HADGEM2_ES (CMIP5), CNRM-CM6-1-HR (CMIP6), and the TerraClimate database to analyze future projections and the specific warming levels (SWLs), respectively. Model data were validated with observed data and bias was removed. A bias correction factor was generated and used in the climate projections for the different emission scenarios. The results show a consensus between the models and the SWLs (2 and 4°C) for the increase in maximum (Tmax) and minimum (Tmin) temperatures for all municipalities in ABC Paulista in different emission scenarios until the end of the 21st century. For the nearest future (2020–2040), the city of São Caetano do Sul (SCS) shows the highest positive annual anomalies of Tmax concerning the climatological period (1985–2015), for the scenario RCP4.5 (2.8°C) and the RCP8.5 (7.4°C), according to projections from the Eta-HADGEM2_ES, highlighting summer and autumn as the hottest. For precipitation, there was a consensus between the Eta-HADGEM2_ES and the CNRM-CM6-1-HR for a reduction in all scenarios and time-slices 2020–2040 and 2041–2070. The municipalities of Diadema (−78.4%) and SCS (−78%) showed the most significant reductions in December for the RCP8.5, and for SSP5-8.5, SCS shows −30.9% in December for the 2020–2040 time-slice. On the other hand, TerraClimate presents excess rain for Ribeirão Pires (+24.8%) and Santo André (+23.7%) in winter for SWL4°C. These results suggest that an increase in Tmax and Tmin, as projected, should influence the intensity of extreme heat events. Furthermore, a reduction in annual and seasonal rainfall does not mean a decrease in the region's extreme daily events that cause floods and landslides. However, it leaves an alert of water scarcity for the supply and demand of the population. ABC Paulista does not have adaptation plans to face extreme climate change. The results can contribute to the first phase of creating an adaptation plan, giving a first view of the climate threat that should intensify until the end of the twentieth century affecting the most vulnerable municipalities.
Keywords: ABC Paulista region; adaptation; CNRM-CM6-1-HR model; Eta-HADGEM2_ES model; future projections; TerraClimate